A pobreza urbana em Parnaíba, Piauí (1890-1920) - Silva, Alexandre Wellington dos Santos (2018)
This dissertation analyzes the “arts of resistance” of the poor people in Parnaiba city, Piauí, between 1890 and 1920. In the first chapter we broach dimensions of Parnaiba’s history, in which we can observe the search for a city pattern inspired by the European urban model, translated in the works of “infrastructure of progress”, placing tensions between the dominant and subaltern ones. In the second chapter we discuss the daily life and housing of the poor people in their quest for survival in insanitary suburbs, a “labyrinth of huts and hovels”, sometimes reached by the Igaraçu River floods. The third chapter socially situates the disease and methods of isolation, demonstrating that certain diseases affected a specific part of the Parnaiban society: the working poor. For this, we consider essential to understand the hygienist discourse, according to theories from that period. The fourth chapter observes instruction practices for poor people in Parnaiba and the struggle against illiteracy and the desire to correct positions that are unfavorable to the idea of progress and modernity. These are public or private schools where teachers strive to teach, usually in some precarious room of their own house. They are Catholic schools where fear of God is preached. They are night schools of the Mutualistic Associations, where they teach many trades and principles of the worker’s morals. It is in the School of Marine Apprentices where the promise of a better life is dissolved by its precariousness and rigid military discipline. In the fifth chapter we analyze the popular, civic and religious festivities, carnival and football in Parnaiba, those moments when the poor workers celebrate in novenas, drumming, or when the neighborhood team wins the “ball game”, almost always awakening the watchful and moralizing look of the many instances of power and control.